Dermatologic Emergencies CME Part I: Inflammatory disorders, angioedema, and anaphylaxis - Mohammed Shanshal (Our Dermatology Online, 2022)
Early detection of erythroderma is essential in clinical practice since the related systemic implications might be fatal. it is characterized by widespread redness with a highly variable degree of scaling. Most of cases have an underlying skin problem or a systemic disorder that is known to be related to erythroderma. idiopathic erythroderma occurs in about 30% of cases. Generalized pustular psoriasis is a rare and life-threatening variant of psoriasis manifests with successive crops of pustules on a background of red and tender skin that covers most of the body. Erythroderma and generalized pustular psoriasis are typically managed with hospitalization, supportive measures, and specialist care.